The Metacognitive Awareness of Reading Strategy Used by College Learners - Anita Anita; Benny Wahyudi (Linguists : Journal Of Linguistics and Language Teaching, 2021)
This research investigated the overall tendency of metacognitive awareness of reading strategies used by college learners in reading academic texts in English. The samples of this research were 25 third semester students of English Study Program at IAIN Bengkulu 2020. Metacognitive Awareness of Reading Strategy Inventory (MARSI) was used to assess adult ESL students’ metacognitive awareness of reading strategy in increasing their reading comprehension. The results showed that the students in this survey are high strategy users in reading. The overall tendency of metacognitive awareness of reading strategies used by college learners in reading academic texts in English was problem-solving strategy (PROB) followed by global reading strategies (GLOB) and the least was support reading strategies (SUP). In the context of EFL students, it showed that problem-solving strategy was the most frequently used strategy. It is proposed to understudies and other readers that they ought to adjust those methodologies in applying them in perusing and be relatively guided by teachers or instructors in utilizing different perusing procedures.